2022
DOI: 10.3389/fmicb.2022.991998
|View full text |Cite
|
Sign up to set email alerts
|

Significant differences in intestinal fungal community of hooded cranes along the wintering periods

Abstract: The intestinal microbiota play vital roles for health of wild birds in many ways. Migratory birds with unique life history might increase the risk of pathogenic transmission across the regions. However, few studies have clarified the fungal community structure and inferred the potential pathogens in guts of migratory birds. The high-throughput sequencing method was applied to analyze the fungal community structure and detect the potential fungal pathogens in guts of hooded cranes among different wintering stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
10
1
Order By: Relevance
“…A higher percentage of these were Lactobacillus , Megamonas , and Enterococcus , which were widely distributed in other birds and were influential in regulating intestinal health, metabolic capacity, and antimicrobial activity ( Gao et al., 2021 ; Zhao et al., 2022 ). Remarkably, we also discovered several genera that are opportunistically pathogenic, including Pseudomonas , Pantoe , Escherichia , Burkholderia , Helicobacter , Fusarium , and Rhodotorula ( Xiang et al., 2019 ; Wang et al., 2020 ; Wu et al., 2022 ). Overall, the data suggested that monitoring the changes in pathogenic species was important for conserving endangered species.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A higher percentage of these were Lactobacillus , Megamonas , and Enterococcus , which were widely distributed in other birds and were influential in regulating intestinal health, metabolic capacity, and antimicrobial activity ( Gao et al., 2021 ; Zhao et al., 2022 ). Remarkably, we also discovered several genera that are opportunistically pathogenic, including Pseudomonas , Pantoe , Escherichia , Burkholderia , Helicobacter , Fusarium , and Rhodotorula ( Xiang et al., 2019 ; Wang et al., 2020 ; Wu et al., 2022 ). Overall, the data suggested that monitoring the changes in pathogenic species was important for conserving endangered species.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the greater relative abundance of Firmicutes may aid in the ability of black-necked cranes to digest and absorb food nutrients and withstand the harsh environment. According to hooded cranes , Ascomycota and Basidiomycota comprised the most fungal species ( Wu et al., 2022 ). To break down complex polysaccharides and enhance the ability of the host to absorb nutrients, several Ascomycota members secret large cellulase and hemicellulase ( Linton, 2020 ; Sun et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studying antibiotic tolerance, we often need to distinguish it from bacterial persistence. Persistence is the ability of bacteria to survive as a small subpopulation of bacteria under high concentrations of antibiotic treatment, and after antibiotic pressure subsides, the persistent bacteria resume growth and regain their antibiotic-sensitive state [34,35]. In contrast, tolerant bacteria survive longer than sensitive bacteria under antibiotic pressure, but they are not unable to be killed, and their population density decreases slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent investigations have more concentrated on the gut fungal community in wild waterbird species [ 8 , 9 , 10 ]. The intestinal fungal community composition of migratory waterbirds may fluctuate due to shifting diets and seasons [ 9 , 11 ], as well as a variety of habitats and captivity conditions [ 12 ]. Although fungi only make up 0.1% of the GIT microbiota [ 13 ], several medical conditions, such as inflammatory bowel disease (IBD), obesity, and allergy problems, have been associated with modifications in the richness and composition of the gut fungal community [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%